Pengaruh Peer Group Bullying Terhadap Psikologi Belajar Aqidah Akhlak Siswa Kelas VII C Di MTS Tarbiyatul Islam Soko Tuban - Manan, Abdul; Khozainul Khoiriyah, Iin (Universitas Islam Lamongan, 2023)
In this study, the problem studied was peer group bullying behavior. This bullying behavior does not look at the age or gender of a person. The purpose of this study was to determine the effect of peer group bullying on the psychology of learning aqidah morals of class VII C students at MTS Tarbiyatul Islam Soko Tuban. This observation uses a field research type of research with a descriptive quantitative approach and simple linear regression analysis. The population taken in class VII C is 32 students. And samples taken from the total population, namely, 32 students. The sampling technique used is non-probability sampling. The results of the study seen from the value of the coefficient of determination (R2) stated that there was a significant positive effect between peer group bullying on learning psychology by 13.6% and the remaining 86.4% influenced by other points of view. Based on the SPSS test, the correlation value is 0.369, with a significance value of 0.019 <0.05, it is stated that there is a correlation between peer group bullying and learning psychology